The Latvian Language as Perceived by Teachers and Students in the 21st Century - Kuzina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The risks to the Latvian language is also Latvian attitude to their own language – vulgarization of language, style diferences, ignoring the elementary language law – the attitude of the state towards the latvian language teaching and research funding. If we talk about Latvian language on 21st century, there could be two forecasts-optimistic and pessimistic. In order to fulfill the optimistic forecast, as consider 76 teachers from high schools of Lielupe and Pumpuri, who had participated in the survey, consider, that Latvian language must remain the only official language status. If the Latvian language will lose the only official language status, then the possible negative forecasts will come true. So 29% of respondents believe in that case, Latvia will lose the Latvian language environment. About 62% of respondents supported the pessimistic forecast. However, like other linquists, I am convinced that Latvian language in 21st century will move a lighter path, that will lead it to further prosperity. In conclusion let us remember the words what an academician J.Stradins said the European Year of Languages conference members:„I wish so the 21st century will not destroy what was built in the 20th century.”